La congruencia de los partidos y los sistemas de partidos multinivel en América Latina: conceptualización y evaluación de algunas herramientas de medición - Došek, Tomáš; Freidenberg, Flavia (Pontificia Universidad Católica del Perú, 2013)
The objective of these article is to evaluate different kinds of methodological tools thatmeasure the levels of congruence of the competition within de multi-level party systems, unders- tanding this last one as the levels of similitude that are experimented by the different districts where political parties compete. It starts from the premise that every party system is multi- level because in that system exists competition in different institutional levels (and in different districts simultaneously). The relevance of multi-level appears when national elections and subnational elections dynamics are not necessarily equals, and it is required to overcome the methodological traditional nationalism that it has been experimented until the moment in the research agenda about parties and party systems. The review of the concept of «congruence» is not exhaustive, and it seeks to systematize the contemporary literature to observe de similarities and differences in national and subnational electoral dynamics, and the consequences of the use of each measurement tool for the identified dynamics.

El objetivo de este artículo es evaluar diferentes herramientas metodológicas para medir los niveles de congruencia de la competencia de los sistemas de partidos multinivel, entendida esta como los niveles de similitud que experimentan entre los diferentes distritos donde compiten los partidos. Se parte de la premisa de que todo sistema de partidos es multinivel, ya que existe competencia en distintos niveles institucionales (y en diferentes distritos de manera simultánea). La relevancia de la lógica multinivel se da en que la dinámicas en las elecciones nacionales y subnacionales no son necesariamente iguales y requieren superar el tradicional nacionalismo metodológico que ha experimentado hasta el momento la agenda de investigación sobre los partidos y los sistemas de partidos. La revisión del concepto de congruencia no es exhaustiva y busca sistematizar la literatura actual para observar las similitudes y diferencias en las dinámicas electorales nacionales y subnacionales, y las consecuencias del uso de cada instrumento de medición sobre las dinámicas que se identifican.
The congruence of political parties and multi-level party systems in Latin America: conceptualization and review of some measurement tools
Keywords: Politics; Political Parties; Multi-Level Party Systems; (In)Congruence Of Party Systems; Congruence’s Measurement Tools; Partidos Políticos; Sistemas de Partidos Multinivel; (In)Congruencia de los Sistemas de Partidos; Medidas de Congruencia; https://purl.org/pe-repo/ocde/ford#5.06.00